Przykłady zintegrowanych zadań szkolnych z języka polskiego dla II klasy gimnazjum = The examples of school tasks meant for the Polish language lesson in the second grade of gymnasium - Kobyłecka, Ewa (Zielona Góra: Uniwersytet Zielonogórski)
Nowadays there can be observed a growing need and search for new, effective and attractive didactic solutions. The perfonning of integrated school tasks activates both cerebral hemispheres of young people. Fostering creative attitudes is a prerequisite for human development.
Keywords: język polski - nauczanie; szkolnictwo ponadpodstawowe